Investigating the Threatening Pollution of the Drinking Water Distribution Network (Case Study: Astara City) - Mohammad Golshan (آب و توسعه پایدار)
Considering the increase in population and the development of urban and rural communities, it is very important to check the quality of urban drinking water. Baharestan watershed supplies most of the drinking water of Astara city with a population of 91,257 people.  In this research, based on laboratory investigations and the Water Safety Plan (WSP), an assessment was conducted on the unintended changes in water quality and the evaluation of the water supply system in this city. For this purpose, after the field visit, the sampling points were determined and samples were taken by depth integration method in three seasons: spring, summer, and autumn. In the sampling points, water quality parameters including sodium, magnesium, calcium, phosphate, nitrate, nitrite, bicarbonate, manganese, iron, chemical oxygen demand, biological oxygen demand, overall digestive form, dissolved oxygen, acidity, electrical conductivity, and total hardness were determined. According to the results, the region's water quality index (IRWQI) was calculated. The results of water quality measurement in the sampling areas showed that the water of this river has no problem in terms of drinking water. The parameter of iron (Fe) with a value of 6.88 mg/liter in the Mashand branch, which has the most sources of pollution, is more than the permissible limit, which indicates the priority of carrying out control and correction measures in this branch. The value of the IRWQI index was equal to 60.33, which indicates the relatively good water condition of the region. Also, the review of WSP results showed that team formation with a score of 65% has the highest score and the average score of this plan in Astara city is 33.64, which means that by completing the WSP plan and preventing pollution from entering the river water, better quality drinking water can be provided to the citizens.